Advancements in Nd:YAG Solar Laser Stability Under Solar Tracking Error Conditions - Catela, Miguel Trindade (2024)
Solar-pumped lasers represent a promising frontier in laser technology, offering the ability to convert incoherent solar radiation into coherent laser radiation without relying on traditional pump light sources. This dissertation explores methods and strategies to develop and adapt solar-pumped laser technology, tailoring it to meet both scientific and industrial challenges. Firstly, solar laser configurations are applied to lamp-pump lasers commonly utilized in indus- try, with the objective of boosting efficiency and brightness while addressing thermal concerns. Additionally, the investigation of alternative beam profiles, such as top hat and doughnut- shaped, showcases the potential of solar lasers in diverse applications, including material pro- cessing and biomedical imaging. Moreover, efforts to improve the stability and efficiency of solar-pumped laser systems, particularly under solar tracking error condition, are discussed. By utilizing end-side pump configurations and incorporating a solar flux homogenizer, significant advancements have been made towards achieving uniform and stable solar laser emissions. Experimental validation of these advancements at the PROMES-CNRS solar facility in Odeillo, France, demonstrates the feasibility of building stable solar laser systems with low-cost solar tracking systems. Even when the tracking system was turned off, the total output power ex- tracted from the solar-pumped laser remained stable for 1 min, representing, to the best of our knowledge, the first successful demonstration of stable multibeam solar laser operation without solar tracking.